1993
DOI: 10.1016/0014-5793(93)80850-t
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of tau protein and Alzheimer paired helical filaments by calcmeurin and phosphatase‐2A

Abstract: We have shown previously that brain tissue contains protein kinases which can phosphorylate tau protein to a state reminiscent of the pathological state of Alzheimer paired helical filaments (PHFs); these include proline-directed kinases which phosphorylate SP or TP motifs (such as MAP kinase and GSK-3) ; Mandelkow et al. (1992)], as well as a novel kinase which phosphorylates S262 of tau protein and thereby strongly reduces the binding of tau to microtubules [Biemat et al. (1993)]. Here we report on the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 40 publications
(56 reference statements)
7
70
1
Order By: Relevance
“…By using the abnormally hyperphosphorylated tau isolated from AD brain as a substrate, we have previously found that PP2A, PP2B, and, to a less extent, PP1 but not PP2C can efficiently dephosphorylate tau in vitro (12,(22)(23)(24). Similar findings have also been reported by using 32 P-labeled tau with various protein kinases as a substrate in vitro (25)(26)(27) or using in vivo phosphorylated tau as a substrate (27)(28)(29)(30). However, to date it is not known which of these three phosphatases regulates tau phosphorylation in vivo and by what mechanism tau is abnormally hyperphosphorylated in AD brain.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…By using the abnormally hyperphosphorylated tau isolated from AD brain as a substrate, we have previously found that PP2A, PP2B, and, to a less extent, PP1 but not PP2C can efficiently dephosphorylate tau in vitro (12,(22)(23)(24). Similar findings have also been reported by using 32 P-labeled tau with various protein kinases as a substrate in vitro (25)(26)(27) or using in vivo phosphorylated tau as a substrate (27)(28)(29)(30). However, to date it is not known which of these three phosphatases regulates tau phosphorylation in vivo and by what mechanism tau is abnormally hyperphosphorylated in AD brain.…”
supporting
confidence: 71%
“…Slices-In vitro studies have suggested that PP2A and PP2B are the best candidate phosphatases involved in the regulation of the phosphorylation of tau (12,(22)(23)(24)(25)(26)(27)(28)(29)(30). Hence, we examined the phosphorylation of tau in these brain tissue slices when either PP2A or PP2B was selectively inhibited.…”
Section: Alzheimer-like Hyperphosphorylation and Accumulation Of Tau mentioning
confidence: 99%
“…and the corresponding phosphatases in the genesis of AD remains to be established. As shown elsewhere [51], both calcineurin and phosphatase-2A can clear the sites affected by the kinases mentioned above. It may be significant that the three proline-directed kinases can be purified as microtubule-associated proteins and are present in neurofibrillary tangles, suggesting that MAPS act as anchors for the kinases and thus are potential targets for them.…”
Section: Exsps Psmentioning
confidence: 99%
“…Analyses conducted on postmortem AD brains have found reduced PP2A expression and activity, and studies conducted in animal models have found that inhibiting PP2A produces AD-like tau pathology and cognitive impairment (1)(2)(3). One of the ways in which PP2A may affect AD is through its role as the principal tau phosphatase (4)(5)(6)(7). PP2A also interacts with a number of kinases implicated in AD including glycogen synthase kinase 3β (GSK3β), cyclindependent kinase 5 (CDK5), and ERK and JNK as well as amyloid precursor protein and the NMDA and metabotropic glutamate receptors (reviewed in ref.…”
mentioning
confidence: 99%